Association between substance use and personality among Mexico City's school children aged 10-13 - Marco Tulio Suárez Maldonado; Guillermina Natera-Rey; Claudia Elena Castillo Lozada (Centros de Integración Juvenil A.C., 2019)
Introduction: substance use is a problem that requires prevention strategies since childhood. It has been noticed that certain personality traits can play an important role in substance use in adolescence and early adulthood. It is essential to study the factors associated with substance use in order to develop and implement preventive interventions. Objective: to evaluate if hopelessness, sensation seeking, impulsivity and anxiety sensibility traits increase the risk of substance use (tobacco, alcohol, marihuana and inhalants) in a group of children enrolled in four primary schools in Mexico City. Methodology: cross sectional exploratory ex post facto survey in which substance use and a personality profile was assessed in a non-randomized sample of 182 children of age 10 to 13. Results: the lifetime prevalence of tobacco, alcohol and other drugs (marihuana and inhalants) use was of 4.4%, 28.6% y 5.5%, respectively. Logistic regression analysis showed that the hopelessness trait significantly increases the risk for use of tobacco (OR = 15.883) and other drugs (OR = 15.090), while the sensation seeking increases the risk of tobacco (OR = 20.856), alcohol (OR = 4.453) and other drugs (OR = 17.139). Discussion: substance use was greater than the estimation in the 2014 Nacional Survey of Drug Use in Students. Hopelessness and sensation seeking play an important role in substance use since late infancy. These results have implications that can help prevention.